The Influence of Audio-Visual Social Media on Knowledge of the Impact of Early Marriage on Adolescent Reproductive Health - Musfiroh, Sri; Triwahyuningsih, Ria Yulianti; Nurjanah, Nunung; Hidayah, Fika Nurul; Rahmatika, Siti Difta; Garbella, Denada (Universitas Padjadjaran, 2025)
Early marriage remains a serious issue that negatively impacts the reproductive health, education, economy, and psychology of adolescents. Ironically, social media often romanticizes this practice, thereby potentially reinforcing misperceptions and reducing reproductive health literacy. The lack of empirical research on the role of social media in shaping adolescents' knowledge about early marriage has created a gap in the literature that needs to be addressed. Lo988 A two-group pretest-posttest pre-experimental research design with a sample of 336 adolescents (168 intervention, 168 control) from SMAN 5 and SMAN 7 Cirebon, selected through simple random sampling. The intervention consisted of health education through animated videos and discussions via WhatsApp. Data were analyzed using the Mann-Whitney test with SPSS. The results showed that the intervention group experienced a significant increase in knowledge after education (p < 0.05), with the majority of respondents before the intervention, 88 people (52.38%), in the “poor” category. after the intervention, 89 respondents (52.98%) were categorized as “adequate” and 74 respondents (44.05%) were categorized as “good.” The control group showed only minimal changes. Therefore, future researchers are advised to develop interventions based on teenage influencers to expand the reach and sustainability of promotion.